Efeitos do treinamento muscular respiratório nos biomarcadores de endotélio e estresse oxidativo em pacientes submetidos à hemodiálise: ensaio clínico randomizado - Campos, Nataly Gurgel (2017)
To analyze the effects of respiratory muscle training (RMT) on respiratory muscle strength, lung function, endothelial / glycocalyx, oxidative stress biomarkers and plasma concentration of endothelin-1 (ET-1) in patients with chronic kidney disease undergoing hemodialysis. Methodology: A randomized controlled trial performed at a Hemodialysis Clinic in the City of Fortaleza, Ceará, from July 2015 to November 2016. The study population consisted of individuals diagnosed with chronic kidney disease enrolled in the hemodialysis sector of the referred clinic. The study included 41 participants in two groups: Intervention Group (IG) with 29 members and the Control Group (CG) with a total of 12 participants. Pulmonary function data were analyzed: maximal inspiratory and expiratory pressures (MIP and MEP) and lung volumes and capacities (Forced Vital Capacity- FVC and Forced Expiratory Volume in the first second- FEV1); Functional capacity: 6-minute walk test (6MWT) and laboratory evaluation of serum levels of endothelial / glycocalyx, oxidative stress biomarkers and ET-1. After the eight week period, in both groups the data above were collected again. The IG training was performed with the ThreshouldPeP device and lasted eight (8) weeks, with a frequency of three (3) weekly sessions, totaling 24 sessions. The first 12 training sessions had a total duration of 30 minutes each, 15 minutes with inspiratory load of 15 cm/H2O and 15 minutes with expiratory load of 15 cm/H2O; And the other 12 sessions had duration of 40 minutes each, being 20 minutes with inspiratory load of 20 cm/H2O and 20 minutes with expiratory load of 20 cm/H2O. All variables were tested for normal distribution. The results were expressed as mean ± standard deviation for continuous variables and frequency and percentage for categorical variables. The changes from the baseline to the eighth week for each study result were evaluated using linear regression maintaining the value of the baseline variable. All models included age, gender, hemodialysis time, body mass index, presence of diabetes mellitus / arterial hypertension and cause of end-stage renal disease as covariates. All analyzes were performed using SPSS 19.0 for Windows (Chicago, IL, USA). The nominal significance level was defined as P <0.05. Results: After eight weeks of the study protocol, the intervention group presented an increase in FVC, FEV1 inspiratory and maximal expiratory pressure in relation to the control group with p <0.001. Compared with the participants in the control group, those in the intervention group achieved a significant reduction in heart rate and mean both baseline and final BP in the 6-minute walk test after RMT. In addition, in the intervention group there was a significant reduction in the modified borg scale (EBM) and an increase in the distance walked in the 6MWT (the difference between the groups at the end of the study adjusted for the baseline was 126.5 meters, 95% CI, 86.1 to 167.0, p <0.001). RMT significantly reduced plasma syndecan-1 levels at 8 weeks compared to CG (between-group difference: -84.5; 95% CI, -148.1 to -20.9). Also, there was a reduction in plasma levels of angiopoietin-2 (between-group difference: -0.48; 95% CI, -1.03 to –0.097). Moreover, 12 there was a significant reduction in mean blood pressure at rest (between-group difference: -12.2; 95%CI, -17.8 to -6.6) associated with a reduction in endothelin-1 levels (between-group difference: -0.164; 95% CI, -0.293 to -0.034). There was no difference regarding biomarkers of endothelial activation or oxidative stress. Conclusion: The proposed short-term respiratory muscle training program improved the respiratory and functional capacity of hemodialytic patients. In addition, there was a significant reduction in endothelial glycocalyx biomarkers (syndecan-1) and Ang 2 (a mediator of angiogenesis and an destabilizer of endothelial cells). Finally, a better control of blood pressure in GI, associated with the reduction in ET-1 levels, was revealed.